If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(1 + 5n) = 120 (1 * -5 + 5n * -5) = 120 (-5 + -25n) = 120 Solving -5 + -25n = 120 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -25n = 120 + 5 Combine like terms: -5 + 5 = 0 0 + -25n = 120 + 5 -25n = 120 + 5 Combine like terms: 120 + 5 = 125 -25n = 125 Divide each side by '-25'. n = -5 Simplifying n = -5
| (5x+2)(5x-1)=0 | | 3x+y-4x= | | 2(2x-7)+3x=21 | | 3p-6=6 | | -2=n-16 | | 8x+2x-4=126 | | (5x+5)-(2+4x)=5 | | y=3x^2-14x+12 | | 4x+2y+y-9x=25 | | (8x^2-2x-38)+(6x^2+4)=0 | | (-5)2-4(5-3)2= | | 6x^2*4x=0 | | 2x(x-2)=5x^2-5x | | 6x^5=-1296x^2 | | 18x^4-18x^2=0 | | 8x=-22 | | 1000/6 | | 6x+5y=1000 | | 4x+x-3x-6x=16 | | cx+ey=d | | r(z^9+3)+(z^9+3)= | | 4x^2+14x+2=0 | | 27=3x+18 | | (4+6i)+(2+6i)= | | 3e^7x=1056 | | 2w=-7/5 | | (M-4/3)-(3m-1/5)=1 | | 3-2i=-12x+4yi | | 4(n+8)+n=6(n-4)+3n | | 4=4x-20 | | 1-4v-2=-25-6r | | (8x+6)(6x^2+6x+6)=0 |